2011
DOI: 10.1007/s12601-011-0012-0
|View full text |Cite
|
Sign up to set email alerts
|

Egg production rate of the copepod Calanus sinicus off the Korean coast of the Yellow Sea during spring

Abstract: The egg production rate (EPR) of Calanus sinicus was measured from March 2007 to April 2010 at three stations along the Korean coast of the Yellow Sea (in coastal waters off Saemangum, Yeongheungdo, and Asan Bay) to estimate in situ maximum egg production rate (MEPR) and to understand whether the females were limited in their growth or fecundity in the field. The mean EPR of C. sinicus at each sampling date ranged from 10.3-34.9 eggs female -1 d -1 (mean 23.4 eggs female -1 d -1 ), and the EPR of individual co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 41 publications
(71 reference statements)
0
2
0
Order By: Relevance
“…The average EPR in this study varied from 2.4 to 44.9 eggs female −1 day −1 (Table 2). In the previous studies on C. sinicus in the Yellow Sea, ranges of average EPR were 1.1 to 6.3 eggs female −1 day −1 from January to November (Zhang et al 2005), 0.2 to 12.6 eggs female −1 day −1 in November (Huo et al 2008), 0 to 25.4 eggs female −1 day −1 in April and October (Wang et al 2009) and 10.3 to 34.9 eggs female −1 day −1 from March to May (Kang et al 2011), respectively. These values and ranges are relatively lower and narrower than our study.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The average EPR in this study varied from 2.4 to 44.9 eggs female −1 day −1 (Table 2). In the previous studies on C. sinicus in the Yellow Sea, ranges of average EPR were 1.1 to 6.3 eggs female −1 day −1 from January to November (Zhang et al 2005), 0.2 to 12.6 eggs female −1 day −1 in November (Huo et al 2008), 0 to 25.4 eggs female −1 day −1 in April and October (Wang et al 2009) and 10.3 to 34.9 eggs female −1 day −1 from March to May (Kang et al 2011), respectively. These values and ranges are relatively lower and narrower than our study.…”
Section: Discussionmentioning
confidence: 93%
“…For Japanese sardine (Sardinops melanostictus) and Pacific round herring (Etrumeus teres), eggs and nauplii of C. sinicus are essential food sources during their early post-larval fish stages (Hirai et al 2017). Therefore, there have been many studies on C. sinicus, e.g., seasonal population dynamics (Kang & Hong 1998, Wang et al 2003, Pu et al 2004, Nonomura et al 2008), long-term population variability (Hidaka & Nakata 2010, Molinero et al 2016, Yang et al 2018, and EPR (Uye & Murase 1997, Park 1997, Wang et al 2009, Kang et al 2011. Among these previous studies, Wang et al (2009) reported a statistically significant relationship between EPR and RI in the Yellow Sea, but their data set covered only spring and autumn.…”
Section: Introductionmentioning
confidence: 99%